“Never too many parks”: the history of Kansas pleasure grounds (1850-1920) - Eshrati, Dorna (Kansas State University, 2020)
Though nineteenth-century parks, also known as “pleasure grounds,” were seen at the time as an antidote to unhealthy high-density urban living in large cities such as New York City, they were embraced by small towns and communities that experienced none of the challenges associated with big city living. Instead, this study argues that parks were seen as a sophisticated sign of modernity. For example, when the state of Kansas was founded in 1861, despite its politically eventful years of the mid-nineteenth century, its settlers felt a strong sense of responsibility and made great efforts to improve their home by creating pleasure grounds for their communities. This study investigates the story of shaping and developing the pleasure grounds of Kansas between 1850 to 1920 and the attitudes that people had about them. Results show that it was not only major cities of the state like Topeka and Wichita that developed public parks for their citizens; many smaller Kansas towns also embraced the idea of creating pleasure grounds. Their residents were motivated by a sense of competition and believed that by beautifying their living environments, they could stand out in the region and attract newcomers. Local newspapers, city officials, businesses – most notably railroad companies, property owners and public-spirited citizens were the main advocates for creating and improving parks in Kansas. Leisure activities, playing sports, and community gatherings were the principal activities in the pleasure grounds of Kansas. Though smaller in size compared to their counterparts in major cities of the United States, the design features of the rural pastoral landscapes of Kansas pleasure grounds were very similar to their east-coast peers and included alternating clusters of trees and meadows, meandering paths, and free-form lakes. The concept of the nineteenth-century pleasure grounds was groundbreaking at the time but has continued to be relevant, as is evident in today’s ubiquitous city parks.
Keywords: Pleasure Ground; Kansas; Kansans; Park; History of Park Design; History of Landscape Architecture